Sejarah Perkembangan Masjid Raya Kota Pematangsiantar, 1911-2017 - Ginting, Andres M.; Anita, Sri Bunga (Mahesa Research Center (PT. Mahesa Global Publishing), 2020)
This article discusses the Pematangsiantar Grand Mosque as the oldest mosque in Pematangsiantar City and Simalungun Regency. This study uses a historical method consisting of stages: (1) heuristics; (2) verification; (3) interpretation; and (4) historiography. The data collection techniques are carried out by: (1) observation; (2) interviews;, (3) document studies; and (4) literature studies. The research results obtained that the Pematangsiantar Grand Mosque is a mosque that was built in 1911 on a 3.977 m2 land grant from the King of Pematangsiantar, namely King Sang Na Ualuh Damanik by the muslim community spearheaded by Panghulu Hamzah, Mr. Syeh H. Abdul Jabbar Nasution , dr. M. Hamzah Harahap Dja Aminuddin. The Grand Mosque has a primary building area of 716 m2 with a capacity of 1.106 people and has two floors. The mosque has parking facilities, parks, worship facilities, warehouses, luggage storage facilities, multipurpose halls, libraries, secretariat offices, air conditioners, multimedia sound systems, power plants/generators, bathrooms, ablution places, joglo or pavilion.Keywords: Pematangsiantar Grand Mosque; history; heritage.